Safe spaces and epistemic character: corruption, resilience and protection in the classroom - Monypenny, Alice (2022)
This thesis offers an account of safety in the classroom and focuses on the relationship between safety and protection. Using a critical character epistemological lens, I argue that a student’s ability to protect themselves from harm may vary in relation to their social positionality or carry significant costs.